Comparison of four diagnostic techniques for detection of Trichomonas vaginalis infection in females attending tertiary care hospital of North India - Razia Khatoon; Noor Jahan; Siraj Ahmad; Haris Manzoor Khan; Tamkin Rabbani (Wolters Kluwer Medknow Publications, 2015)
Background: Trichomonas vaginalis causes a common sexually transmitted disease trichomoniasis, which may lead to increased risk of transmission of human immunodeficiency virus infection and other pelvic inflammatory diseases. Wet mount examination is the most common test for diagnosis, but it has low sensitivity. Acridine orange staining can be used for diagnosis, but it requires special microscopic facility. Culture is considered as the gold standard, but it takes a long time for diagnosis. OSOM Trichomonas Rapid Test is a recently introduced rapid method based on immunochromatographic assay of trichomonal protein antigens. Hence, the present study was done to compare these four diagnostic techniques for detection of trichomoniasis in females with vaginal discharge. Materials and Methods: Vaginal swabs were taken from 835 female patients and wet mount examination, acridine orange staining, culture in Kupferberg medium, and OSOM Trichomonas Rapid Test, were performed. Results: Out of 835 patients included in our study, 68 (8.1%) positive cases of trichomoniasis were detected by culture. OSOM Trichomonas Rapid Test detected 63 (7.5%) cases, acridine orange staining detected 53 (6.3%) cases, whereas, wet mount examination detected only 45 (5.4%) positive cases. OSOM Trichomonas Rapid Test performed well and showed high sensitivity and specificity of 88.2% and 99.6%, respectively. Conclusion: As OSOM Trichomonas Rapid Test is a point of care test and gave better results than both wet mount examination and acridine orange staining; it can be used as a routine test in peripheral areas lacking laboratory facilities.